Eagle's Syndrome - Pinheiro, Thaís Gonçalves; Soares, Vítor Yamashiro Rocha; Ferreira, Denise Bastos Lage; Raymundo, Igor Teixeira; Nascimento, Luiz Augusto; Oliveira, Carlos Augusto Costa Pires de (International Archives of Otorhinolaryngology, 2013)
Introduction: Eagle's syndrome is characterized by cervicopharyngeal signs and symptoms associated with elongation of the styloid apophysis. This elongation may occur through ossification of the stylohyoid ligament, or through growth of the apophysis due to osteogenesis triggered by a factor such as trauma. Elongation of the styloid apophysis may give rise to intense facial pain, headache, dysphagia, otalgia, buzzing sensations, and trismus. Precise diagnosis of the syndrome is difficult, and it is generally confounded by other manifestations of cervicopharyngeal pain.Objective: To describe a case of Eagle's syndrome.Case Report: A 53-year-old man reported lateral pain in his neck that had been present for 30 years. Computed tomography (CT) of the neck showed elongation and ossification of the styloid processes of the temporal bone, which was compatible with Eagle's syndrome. Surgery was performed for bilateral resection of the stylohyoid ligament by using a transoral and endoscopic access route. The patient continued to present pain laterally in the neck, predominantly on his left side. CT was performed again, which showed elongation of the styloid processes. The patient then underwent lateral cervicotomy with resection of the stylohyoid process, which partially resolved his painful condition.Final Comments: Patients with Eagle's syndrome generally have a history of chronic pain. Appropriate knowledge of this disease is necessary for adequate treatment to be provided. The importance of diagnosing this uncommon and often unsuspected disease should be emphasized, given that correct clinical-surgical treatment is frequently delayed. The diagnosis of Eagle's syndrome is clinical and radiographic, and the definitive treatment in cases of difficult-to-control pain is surgical.
Keywords: Neck Pain; Osteogenesis; Oral Surgical Procedures